Factors Associated with Higher Rates of Heterotopic Ossification After Spinal Cord Injury: A Systematic Review and Meta-Analysis. (16th November 2020) - Yolcu, Yagiz U; Wahood, Waseem; Goyal, Anshit; Alvi, Mohammed A; Reeves, Ronald; Qu, Wenchun; Gerberi, Danielle; Goncalves, Sandy; Bydon, Mohamad
Abstract: INTRODUCTION: Heterotopic Ossification (HO) refers to the formation of bone within soft tissue. Traumatic spinal cord injury (SCI) has been shown to be associated with development of HO. However, risk factors for HO following SCI are unknown. METHODS: An electronic literature search was conducted using five databases.Studies containing SCI patients, with a proportion diagnosed with HO, were included. Meta-analyses were performed to assess the association between following risk factors and development of HO: sex, type of injury, spasticity, pressure ulcer, injury level, urinary tract infection (UTI), deep vein thrombosis (DVT), number of smokers, and pneumonia. RESULTS: Nine studies with 2, 115 patients were included. It was found that males (Odds Ratio [95% Confidence Interval]: 2.25 [1.61, 3.13]), smokers (2.88 [1.62, 5.11]), patients with complete injury (3.61 [2.29, 5.71]), pneumonia (2.86 [2.18, 3.75]), pressure ulcers (2.45 [1.89, 3.18]), UTI (3.84 [2.63, 5.62]) and spasticity (2.12 [1.67, 2.68]) had significantly higher odds of developing HO after spinal cord injury. In contrast, location of injury (Cervical vs. thoracic injury; (1.03 [0.72, 1.49]) and DVT (1.37 [0.91, 2.07]) were not associated with development of HO. CONCLUSION: Pooled results from existing literature on HO development show that several factors are significantly associated with development of HO. Given the complexity of SCI management, the results might have a positive impact on the clinical practice by leading to an effective screening aproach.